Efficiency of Fully-automatic Dividing and Packing Machine Model OMP-Z - ISHIKURA, CHIYOJI; SAMIZO, KAZUO; ISHIZUKA, HIDEO; HORIGUCHI, MASAMI (Byōin yakugaku, 1986)
A new fully-automatic dividing and packing machine model OMP-Z (Tokyo Shokai) for powder and granule drugs was tested for a) error of dividing weight, b) accuracy of dividing weight in relation to the physical properties of the drug to be divided and packed, c) accuracy of dividing weight in relation to the number of subpacks and the quantity in each subpack, d) the rate of loss, and e) contamination. The mean coefficient of variation (C. V.) of 21 drugs was 2 to 3% for 14 subpacks of 1 g in theoretical weight. This variation was lower than those of the existing fully-automatic dividing and packing machines. The rate of loss ranged from 0 to 24.8%, and was 3% or less for most drugs. However, it increased with drugs which were very adhesive. The results of the tests were analyzed in relation to the angle of repose and dustability of the drugs. Errors in dividing weight were correlated with the angle of repose. They tended to become greater with an increased angle of repose. The accuracy of dividing weight was examined in relation to the number of subpacks and the quantity in each subpack. 14, 28 and 42 subpacks of 0.5, 1.0, or 2.0 g in theoretical weight were prepared from 6 drugs. In some of these drugs, errors in dividing weight increased with smaller dose in each subpack and a greater number of subpacks. Contamination was tested as follows: Lactose stained with eosin was first divided and packed, followed by the dividing and packing of lactose without eosin staining. The content of eosin in the subpacks of lactose without eosin staining was measured by means of spectrophotometry. The mean content of eosin was 3.5%. In summary, the machine will be practical in use if the features of the machine are fully understood although some points still remain to be improved.